PRODUCING COOLING FROM SOLAR ENERGY BY USING ADSORPTION CYCLE WITH ACTIVATED CARBON AND METHANOL PAIR - Himsar Ambarita (Jurnal Dinamis, 2011)
AbstractIndonesia is blessed with abundant supply of solar energy which can be harvested in awhole year. According to Ministry of Energy and Mineral Resources Republic of Indonesia, totalenergy of solar radiation in Indonesia varies between 16 - 18MJ/m2/day. A refrigeration machinewith adsorption cycle is an alternative that can be used to collect the solar energy and use it toproduce cooling. This paper deals with design, fabrication, and testing a small scale solarpoweredadsorption cyle refrigeration machine. It consists of condenser, evaporator, absorberand generator. The absorber has a surface area of 0.25 m2 and it is loaded with 6 kg localproduced activated carbon, as a generator. The evaporator is filled with 2 litres of methanol asrefrigerant. The refrigeration machine has been tested by exposing directly to solar radiation inMedan city. Using data acquisition system, operational temperatures and solar radiations aremeasured and collected. The results show that solar radiation can heat the absorber up to120oC. Thus the methanol is desorbed from the activated carbon and condensed by condenserand sent it back to evaporator. During night, the methanol is absorbed from evaporator andproduces cooling. The lowest temperature can be reached here is 10oC. The conclusion can bedrawn here is that solar radiation can be used to produce cooling in a very simple way andwithout any moving part.Keywords: renewable energy, solar, refrigeration, adsorption